The Impact of STEM Education on Science Education Student’s Creative Thinking Skills on The Concept of Genetic Engineering: Case Study - Meliyana Aini; Wida Salupi; Mellyatul Aini; Zakaria Sandy Pamungkas; Ratna Yulinda (Jurnal Pendidikan Vokasi Indonesia, 2025)
The concept of genetic engineering is one of the most difficult materials students can understand. It's because it’s very abstract and its existence is microscopic, so it takes educator skills to make it easier for students to understand the concept of genetic engineering. Understanding is much easier when it comes to using the issues that are in society and corroborating the concept of genetic engineering in prototype form. STEM education is one of the approaches that can help educators in developing creative thinking skills of science education students. The purpose of this research is that STEM education has an impact on the creative thinking skills of science education students on the concept of genetic engineering. Using a quantitative method by taking the average of student sheets and creative prototype genetic engineering by science education students. The average is rated according to 4 creative thinking skills indicators. Research shows the average creative thinking skills is 85.2% with excellent categories. As a results, students can think creatively to solve the problem of genetic engineering that happens in society. And understanding the concept of genetic engineering is easier for students to understand by using prototypes so misconception can be avoided. The conclusion of this research is the impact of STEM education can grow the creative thinking skills of science education students on understanding the concept of genetic engineering.